Coordinated lightning, balloon‐borne electric field, and radar observations of triggered lightning flashes in North Florida. Issue 13 (14th July 2015) - MacGorman, D. R.; Biggerstaff, M. I.; Waugh, S.; Pilkey, J. T.; Uman, M. A.; Jordan, D. M.; Ngin, T.; Gamerota, W. R.; Carrie, G.; Hyland, P.
Abstract This study examines coordinated storm and triggered lightning observations made in July–August 2013 at the International Center for Lightning Research and Testing to determine why triggered flashes in Florida typically transition from an upward vertical channel entering the cloud to horizontal structure near the storm's melting level. Data from a balloon‐borne electric field meter, a mobile 5 cm wavelength radar, and a small‐baseline VHF Lightning Mapping Array acquired during a period in which three flashes were triggered on 1 August confirmed the hypothesis that the transition to horizontal lightning structure just above the melting level occurred in a layer of negative charge. This experiment was the first to provide vertical profiles of the electric field in Florida storms, from which their vertical charge distribution could be inferred. Three dissipating storms observed on different days all had negative charge near the melting level, but a growing mature storm had positive charge there.